A Comprehensive Study of the Olonkho: Discussion and Perspectives - Sivtseva-Maksimova, Praskovia Vasilyevna (Journal of History Culture and Art Research, 2018)
There is an increasing interest on the creative features of the Yakut epic olonkho in current literature. The article gives special focus to acknowledged researches of distinguished scholars who studied the oral epic heritage of the Sakha people. An overview of these researchers’ works and their methodology is achieved with the following goal - to single out rationalized scientific approaches in the process of typological systemization of the Yakut epic based on the structural analysis of the olonkho plots and images; to explain the substantiated ideas expressed in complex research monographs by I.V. Pukhov, N.V. Emelyanov, A.P. Reshetnikova, and D.T. Burtseva as a systematic in-depth text analysis of the oral traditional art. In these aspects, there is a range of specific foundations that form the olonkho; this is explained in the research works in the form of plot classification and a fixed systemization of the main images together with a complex typological study of the unity of two planes - the epic content plane and the oral expression plane. The main dogmas of the research completed by Yakut scholars is advocated through the prism of theoretical issues and fundamental problems reflected in the works by Aristotle, H.W.F. Hegel, A.N. Veselovsky, E.M. Meletinsky on the aesthetics and poetics of oral forms of language art. Research results expand the range of possibilities of holding a complex study of epic, which does not exclude the possibility for scientific discussions. Perspectives for a complex olonkho research are in the fact that these research works reveal the creative onsets of the ancient oral art texts in a polyphonic concordance and in equal amounts. This is the conventionality in expressing the reality in its pure form, the inner completeness of a unified expression of the idea; and the originality, all of which cannot simply be taught; the uniqueness, equal to universality; the initial natural address towards the listeners, which can be equaled to the creative foundations of olonkho as one of the examples of unique epic storytelling forms.